UKRAINIAN HISTORICAL, ARCHITECTURAL AND MUSEUM POTENTIAL FOR SUCCESSFUL EUROPEAN CULTURAL INTEGRATION (Південний архів (історичні науки), 2022)
For the near future of our Ukraine, an important direction of international cooperation, first of all, with neighboring states – with Poland, Slovakia, Hungary, Romania, will be cultural. Today, this type of cooperation is impossible due to Putin’s aggression on our lands. The purpose of this work is to characterize the historical, architectural and museum potential of the western regions of Ukraine (Lviv, Zakarpattia, Ternopil, Ivano-Frankivsk, Volyn, Chernivtsi, Rivne) for the formation and development of modern, successful European cultural integration. The historiographical basis of the specified question was studied using the chronological method from the time of independence of Ukraine to the present day, and the characteristics of the museum and historical-architectural funds of the largest cities of western Ukraine were studied using the descriptive method. Results. Regarding the analysis of the historiographical basis of the question, Ukrainian-Polish cultural cooperation in various aspects (regional, educational, scientific, humanitarian, etc.) was studied. Lviv, Zakarpattia, Ternopil, Ivano- Frankivsk, Volyn, Chernivtsi, and Rivne regions have extremely rich historical, architectural and museum potential for successful Ukrainian-European cultural cooperation. Conclusions. There are a lot of museums, they are diverse in terms of content, and therefore every European tourist can find something necessary and useful. As for the historical and architectural potential of the named regions, the vast majority of objects that represent value are religious buildings, mostly active, for local believers (churches of the Orthodox Church, Roman Catholic, Greek Catholic, Jewish, Armenian, etc.). The material base for Ukrainian-European cultural cooperation is sufficient to satisfy the spiritual needs of believers of various faiths, as well as atheists, connoisseurs of history and culture, and will contribute to the acceleration of the process of European integration.
Keywords: architectural, museum fund, European integration, international communication, cultural cooperation